Network of Mosque Bazar (NOMBazar) - conceptual online platform for house rental, laundry and cleaning service, Halal food Mart - Mohd Suhimi, Muhammad Firhad; Ajahar, Amirul Hakim; Ahmad Dahlan, Abdul Rahman (Research Publisher, 2018)
With the technology arise in this era, most people love to do everything online. Even now, there are many apps that can help in connecting people to something they want to buy and purchase. This conceptual paper proposes the NOMBazar Online Marketplace, which is to help people to do business in renting their properties through digital platforms, do business in selling halal food and offer maid, laundry and cleaning services. This paper will discuss the business model canvas and value proposition canvas.